KONFLIK KEKERASAN, OTONOMI DAERAH DAN INTEGRASI NASIONAL - Anggoro, Dr Kusnanto (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2010)
In a decade of reform, several changes had been occurred. Some adjustments could be considered as success, while others potentially could trigger conflicts. Historical conflict remnants in Indonesia were hard to restrain. Hence, national integration remains crucial in foreseen future. Local autonomy could be an avenue to resolve problem of national integration in particular context. However, local autonomy could result in reverse end. In the midst of conflict pattern change and development over last decade, bureaucracy (local and national) has to be able to foresee any sign of conflict (early warning) in order to be able to anticipate. Conflict recognition could be observed through various indications, ranging from demographic changes, deterioration of social economic situation, and/or cultural tensions. Failure to do corrective action on such deviation would lead to greater risk of conflict occurrence